ChemInform Abstract: Core—Shell AgNP@CeO2 Nanocomposite Catalyst for Highly Chemoselective Reductions of Unsaturated Aldehydes. Issue 37 (22nd August 2013) - Mitsudome, Takato; Matoba, Motoshi; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract Different unsaturated aldehydes are hydrogenated by using the title nanocomposite (17 examples).